Considerations in the Design, Installation and Operation of a Complete Sounding System - Steenstrup, Per Resen (The International Hydrographic Review, 2015)
This paper is concerned with the various parameters which are critical in order to achieve an optimal echo sounding system for a specific application. A number of practical examples are explained. Echo sounding systems have a tendency to be so general, that it is important the user understands how to select the right type of echo sounding system for his application. The paper only deals with the acoustic and analog signal handling, whereas the digital handling, which is mainly a software problem, is not discussed here. Special attention is given to the right choice of transducer for a specific job and its installation.